BİR VAKIF ÜNİVERSİTESİ TIP FAKÜLTESİ HASTANESİ FİZİKSEL TIP VE REHABİLİTASYON SERVİSİ'NİN MALİYET YAPISI VE ANALİZİ - (:unkn) unknown (My University, 2015)
Bu araştırmanın amacı, geçmişte uzun yıllar idari ve mali açıdan kamu müessesesi niteliğinde hizmet veren, günümüzdeyse bir vakıf üniversitesine bağlı Tıp Fakültesinin Fizik Tedavi ve Rehabilitasyon (FTR) Anabilim Dalına ait bakım ve tedavi servislerinin maliyet yapısı ve analizidir. Çalışmada, Vergi Usul Kanunu ve diğer ilgili mevzuat gereğince tutulan kayıt ve raporlara dayalı muhasebe verileri kullanılmıştır. Bunlar, Microsoft Excel programı kullanılarak geleneksel yöntemlerle çözümlendikten sonra, bilgisayar istatistik programında Korelasyon (ilişki) testi yapılmış, veri güvenliğiyse Alfa testiyle yapılmıştır. Toplam maliyetin yarısından fazlasının işgücü giderinden oluşmasına rağmen, bu iki değişken/gider arasında anlamlı bir ilişki bulunamamıştır.

This study aims to analyze the structure of the cost caused by inpatients or outpatients that receive service at the care and treatment units of the Physical Therapy and Rehabilitation Department of the Medical Faculty of a foundation university, which provided service as  a public enterprise for long years both in administrative and economic terms. Accounting data of the patients who underwent treatment in PTR services based on records and reports dated May 2012 and January 2013 maintained by general accounting of the hospital in accordance with tax and other relevant legislation.After resolving the data by conventional methods using Microsoft Excel program, correlation test was done using statistical program, also Alpha test was done in terms of data security. Although more than half of the total cost belonging to PTR services is comprised of labor cost , a significant correlation was not found between these two variables. On the other hand, a significant and positive correlation was found between public service production costs including the purchase of services through the use of outsourcing services and the use of materials and supplies . Similar findings were determined by total income .
COST ANALYSIS OF PHYSICAL MEDICINE AND REHABILITATION SERVICE OF MEDICAL FACULTY HOSPITAL IN A FOUNDATION UNIVERSITY
Keywords: İktisat; İşletme